Women’s Roles in Iḥyā’ ‘Ulūm al-Dīn and Method of Teaching it at Pesantrens in Indonesia - Umma Farida; Abdurrohman Kasdi (Al-Jami'ah Research Centre, 2021)
The study examines the portrayal of women’s roles in the marriage from the Islamic classical book Iḥyā’‘Ulūm al-Dīn written by Abu Hamid al-Ghazali which is widely taught at Pesantrens in Central Java, Indonesia. The interpretation of this book has a significant impact on the thinking, mindset, personality, and attitudes of Pesantrens communities. This research first uses the library-based method, analyzing the literature on Iḥyā’ ‘Ulūm al-Dīn and using the qualitative-interpretative approach in understanding the text regarding women’s roles in marriage. Secondly, the research examines how Iḥyā’ ‘Ulūm al-Dīn is taught in three Pesantrens in Central Java. The result shows that al-Ghazali›s view of women in Iḥyā’ is different from his views before isolation. In Iḥyā’, the patriarchal language is sensed. The common use of al-Ghazali’s monumental work in Pesantren is in the Bandongan (teacher-centered) method without any criticism in teaching about women’s roles in marital relations. Even though Iḥyā’ is not the only source of imbalance of the roles of women and men in marriage, but it does contribute to it by becoming an unquestioned authoritative source on these contemporary issues in the Pesantrens. Therefore a methodical improvement in the learning process becomes a necessity by using the active learning strategies into active-Bandongan methods that can increase the activeness of the teaching and learning process carried out either by teachers or students to produce dynamic and contextual creative thoughts. [Tulisan ini membahas gambaran peran perempuan dalam pernikahan berdasar kitab Ihya’ yang ditulis Abu Hamid al-Ghazali yang mana pengajarannya meluas hingga pesantren di Jawa Tengah. Penafsiran terhadap kitab ini berimplikasi pada pemikiran, sudut pandang, karakter dan sikap komunitas pesantren. Pendekatan yang digunakan dalam kajian ini adalah studi literatur dan kualitatif interpretatif dalam pemahaman teks dalam kitab yang terkait tema peran perempuan dalam keluarga. Selain itu juga pengamatan pada tiga pesantren di Jawa Tengah yang mengajarkan kitab ini. Kesimpulan yang muncul adalah adanya pandangan dan bahasa al-Ghazali yang cenderung patriakal. Karya penting al-Ghazali yang banyak diterapkan di pesantren adalah metode bandongan, yang mana kurang mengapresiasi kritisme dalam melihat peran perempuan dalam hubungan perkawinan. Meskipun Ihya’ bukan satu-satunya sumber sumber referensi, tapi telah menjadi otoritatif yang tidak dipertanyakan lagi di dunia pesantren saat ini. Oleh karena itu pengembangan metode pengajaran menjadi penting dengan penggunaan strategi pembelajaran metode bandongan aktif, baik bagi guru dan murid untuk memproduksi dinamika dan pemikiran kreatif kontekstual.]